Performance Evaluation of Mutual Funds in Pakistan for the Period 1998 - 2008. - Keshwani, Faysal (2008)
Mutual Funds around the world have attracted trillions of dollars and millions of investors. Given the importance of the industry, performance evaluation of mutual funds has become the most commonly discussed topic in finance. Mutual Funds in Pakistan have recently become the centre of attraction for both practitioners and academics since the mutual fund industry has recently started to develop, and it has been hardly four to five years since most of the open-ended funds have been introduced. The assets under management of open-ended funds have swelled from PKR 25 billion in 1997 to PKR 340 billion in 2008. This paper attempts to examine the performance of newly introduced and rapidly growing open-ended funds in Pakistan, though some funds have been in existence for long. The study uses pioneering models of Mutual Fund performance proposed by Sharpe (1966), Treynor (1965) and Jensen (1967). The results of the evaluation indicate the performance of the funds being quite negative. But the performance evaluation also reveals some positive characteristics of the funds which have been discussed in the paper. Naturally, since most of the funds have hardly completed around three to four years of their operation, it is too early to conclude whether the overall performance of the industry is good or bad.